Sequencing and analysis of common bean ESTs. Building a foundation for functional genomics - Ramírez, M.; Graham, MA; Blanco Lopez, L; Silvente, S; Medrano Soto, A; Blair, Matthew W.; Hernández, G.; Vance, CP; Lara, M (Oxford University Press, 2005)
Although common bean (Phaseolus vulgaris) is the most important grain legume in the developing world for human consumption, few genomic resources exist for this species. The objectives of this research were to develop expressed sequence tag (EST) resources for common bean and assess nodule gene expression through high-density macroarrays. We sequenced a total of 21,026 ESTs derived from 5 different cDNA libraries, including nitrogen-fixing root nodules, phosphorus-deficient roots, developing pods, and leaves of the Mesoamerican genotype, Negro Jamapa 81. The fifth source of ESTs was a leaf cDNA library derived from the Andean genotype, G19833. Of the total high-quality sequences, 5,703 ESTs were classified as singletons, while 10,078 were assembled into 2,226 contigs producing a nonredundant set of 7,969 different transcripts. Sequences were grouped according to 4 main categories, metabolism (34%), cell cycle and plant development (11%), interaction with the environment (19%), and unknown function (36%), and further subdivided into 15 subcategories. Comparisons to other legume EST projects suggest that an entirely different repertoire of genes is expressed in common bean nodules. Phaseolus-specific contigs, gene families, and single nucleotide polymorphisms were also identified from the EST collection. Functional aspects of individual bean organs were reflected by the 20 contigs from each library composed of the most redundant ESTs. The abundance of transcripts corresponding to selected contigs was evaluated by RNA blots to determine whether gene expression determined by laboratory methods correlated with in silico expression. Evaluation of root nodule gene expression by macroarrays and RNA blots showed that genes related to nitrogen and carbon metabolism are integrated for ureide production. Resources developed in this project provide genetic and genomic tools for an international consortium devoted to bean improvement.